Influence of Phase Change Material Physicochemical Properties on the Optimum Fin Structure in Charging Enhancement - Benli Peng (AIDIC Servizi S.r.l., 2021)
Orthogonal fins made of a vertical and a horizontal fin shorten total charging time and enhance average charging rate of lowly conductive phase change materials (PCMs) such as paraffin wax. An optimum dimension of orthogonal fins exists during charging of paraffin wax under top heating. The optimum dimension is represented by the optimum relative distance. The relative distance d/lv is defined as the ratio of the distance between horizontal fin and bottom wall of enclosure to length of vertical fin. However, the physicochemical properties of PCMs are variant in practical. Their influences on this optimum relative distance of orthogonal fins are not conducted. In current investigation, the investigations on influence of PCMs’ physicochemical properties on the optimum relative distance of orthogonal fins are numerically carried out. Influences of PCMs’ physicochemical properties including thermal conductivity, thermal expansion coefficient and viscosity on the optimum relative distance of the orthogonal fins are analysed. Results demonstrate that these physicochemical properties significantly influence the optimum relative distances. The optimum relative distance decreases from ~0.1633 to ~0.1020 when thermal conductivity increases from 0.1 W·m-1·K-1 to 1.5 W·m-1·K-1. When thermal expansion coefficient of PCM increases from 0.0001 K-1 to 0.005 K-1, the corresponding optimum relative distance decreases from ~0.1877 to ~0.0816. When viscosity of the liquid PCMs increases from 0.2 mPa·s to 80 mPa·s, the optimum relative distance of orthogonal fins increases from ~0.1224 to ~0.2245. The results supply an effective guideline to design an optimum orthogonally structured fins to enhance the average charging rate of organic PCMs with random physicochemical properties.